Mucoepidermoid carcinoma of the vermillion border of the upper lip: A rare occurrence - Renuka Masodkar; Ganesh Jadhav; Sapna Verma (Apollo Medicine)
Mucoepidermoid carcinoma (MEC) is a rare tumor. Very few cases of MEC of the upper lip have been reported in the literature. We report a case of 34-year-old female with MEC of the upper lip treated with surgery and postoperative radiotherapy.